Benjamin Robbins Curtis papers - Curtis, Benjamin Robbins, 1809-1874.
Three volumes containing correspondence and several legal papers dealing primarily with legal and judicial matters during his service as U.S. Supreme Court justice and his practice of law in Massachusetts. Subjects include the Dred Scott case and political affairs. Correspondents include Roger S. Baldwin, Charles Henry Bell, John Archibald Campbell, George Ticknor Curtis, William W. Greenough, Samuel Nelson, Roger Brooke Taney, George Ticknor, and Daniel Webster.
Lawyer and jurist.
Collection material in English.
Keywords: Baldwin, Roger S. -- 1793-1863 -- Correspondence; Bell, Charles Henry, -- 1823-1893 -- Correspondence; Campbell, John Archibald, -- 1811-1889 -- Correspondence; Curtis, George Ticknor, -- 1812-1894 -- Correspondence; Greenough, William W. -- -1899 -- Correspondence; Nelson, Samuel, -- 1792-1873 -- Correspondence; Scott, Dred, -- 1809-1858 -- Trials, litigation, etc; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Ticknor, George, -- 1791-1871 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; United States. -- Supreme Court; Practice of law -- Massachusetts; United States. -- Politics and government; Jurists; Lawyers